Ice Loads and Ship Response to Ice. Summer 1982/Winter 1983 Test Program - St. John, J. W.; Daley, C.; Blount, H. (1984)
Work toward development of local ice load criteria for icebreaking ships is presented. A bow panel of approx. 100 sq ft was instrumented to measure ice pressures by measuring compressive strains in the webs of transverse frames. The panel was divided into 60 sub-panel areas, 6 rows of 10 frames, over which uniform pressures were calculated during an impact with ice. A digital data acquisition system recorded only events over a present threshold strain. A microprocessor controlling data acquisition allowed real time data to be streamed through memory such that the recorded data were the 60 channel strain time-history from 1 sec before to 4 sec after the threshold was exceeded, sampling each channel at 32 Hz. Approximately 1400 such events were recorded on two deployments, one to the Beaufort Sea in Sep-Oct 1982 recording summer multiyear ice impacts and one to the Chukchi Sea in Mar-Apr 1983 recording both first year and multiyear winter ice impacts. All strain data were converted to pressure time-histories over each of the 60 sub-panels. Finite element models of the hull structure were used to develop a data reduction matrix relating measured strains to uniform pressures. The result is a spatial and time representation of each impact. Extreme pressure area curves were developed for each event. Extreme envelopes of pressure vs. area were were developed from data for each of 5 areas; south and north Bering Sea, South and north Chukchi Sea, and Beaufort Sea. Trends in peak force and peak pressure are examined in terms of ship impact speed and ice conditions. Prepared in cooperation with ARCTEC, Incorporated, Columbia, MD and ARCTEC Canada Limited, Kanata, Ontario, CA.